HPTLC FINGERPRINTS AND FTIR ANALYSIS FOR AUTHENTICATION AND QUALITY CONTROL OF Holostemma ada-kodien Schult. (Applied Biological Research, 2024)
Plant-derived pharmaceuticals are gaining increased acceptance in treating   various ailments, but ensuring their quality is crucial. Both conventional and   modern techniques are employed to validate the quality. High performance   thin layer chromatography (HPTLC) and Fourier transform infra-red (FTIR)   analysis were conducted to analyse and identify the various phytoconstituents   in serial root extract of Holostemma ada-kodien. The peaks observed in   HPTLC fingerprint profile corresponding to different phytoconstituents   served as markers for standardizing drug; while FTIR analysis aids in   identifying the major functional groups present. Thirteen bands were noted for hexane extract of H. ada-kodien in short UV in track I, while chloroform   and methanol extracts showed eight bands each. In track II, the hexane extract   exhibited eight bands, while chloroform and methanol extracts showed eleven  and eight bands, respectively, under similar conditions. The hexane extract in   long UV showed a maximum area of 78.4 and 71.59%, in track 1 and 2,   respectively, with respective spanning from Rf 0.61 to 0.75 and 0.51 to 0.73.  The methanol extract in visible light in track I showed a maximum area of   46.87%, spanning from Rf 0.73 to 0.98, and in track II, it displayed a maximum   area of 36.59%, spanning from Rf 0.75 to 0.96 with 10 µL applied. Methanolic  root extract of H. ada-kodien showed clear banding patterns in HPTLC   fingerprints which seemed to be a dependable technique to detect adulteration   while FTIR technique revealed functional groups of methanol root extracts.
Keywords: Holostemma ada-kodien; HPTLC; FTIR analysis; authentication